From Illustration to Evidence: Centring Historical Photographs in Native Land Claims: A conversation with Michael Aird - Aird, Michael (Kronos: Southern African Histories, 2021)
My main research area is the region surrounding Brisbane, the capital city of the State of Queensland. I particularly concentrate on the region within about 100 kilometres of the city, but at times I document individuals that may have come from 200 or 300 kilometres away, if these people had some sort of connection to Aboriginal families that lived closer to Brisbane.